Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-238
|View full text |Cite
|
Sign up to set email alerts
|

External Heat Transfer Predictions in a Highly-Loaded Transonic Linear Turbine Guide Vane Cascade Using an Upwind Biased Navier-Stokes Solver

Abstract: External heat transfer predictions are performed for two-dimensional turbine blade cascades. The Reynolds-averaged Navier-Stokes equations with algebraic (Arnone and Pacciani, 1996), one-equation (Spalart and Allmaras, 1994) and two-equation (low-Re k-ε, Biswas and Fukuyama, 1994) turbulence closures are solved with a fully-implicit time-marching finite volume method. Comparisons with measurements (Arts et al., 1990, 1994) for a highly-loaded transonic turbine nozzle guide vane cascade show good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The eddy viscosity is modelled using the oneequation turbulence model of Spalart and Allmaras (1994) and the low-Reynolds-number k-ε model of Biswas and Fukuyama (1994). Both models were validated against simple flows, such as a flat plate boundary layer and showed good agreement with published experimental results (Artner, 1997, Gehrer and Jericha, 1999, Gehrer 1999). Spalart-Allmaras (1994).…”
Section: Numerical Approachmentioning
confidence: 80%
See 1 more Smart Citation
“…The eddy viscosity is modelled using the oneequation turbulence model of Spalart and Allmaras (1994) and the low-Reynolds-number k-ε model of Biswas and Fukuyama (1994). Both models were validated against simple flows, such as a flat plate boundary layer and showed good agreement with published experimental results (Artner, 1997, Gehrer and Jericha, 1999, Gehrer 1999). Spalart-Allmaras (1994).…”
Section: Numerical Approachmentioning
confidence: 80%
“…Navier-Stokes Solver. The flow solver used in this work is based on the time-marching Euler code of Sanz et al (1995) and described in detail by Gehrer (1999). Here only a brief outline of the main features of the Navier-Stokes code is given.…”
Section: Low Reynolds Number K-ε Model Ofmentioning
confidence: 99%
“…Based on this state-of-the-art, this paper proposes to investigate the prediction of heat transfers in a highly loaded turbine guide vane, by means of structured and unstructured flow solvers. The test case is a well documented configuration [11] representative of a modern turbine blade and extensively used for CFD validation [3,12]. The first section of the paper details the main parameters of this configuration.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, algebraic turbulence models (the Baldwin-Lomax [3][4][5][6] or the Mitchel one [7]), one-equation models (the Spalart-Allmaras one [5; 7]) and two-equation (k − or k − ! ones, see References [6][7][8]) have been used for the analysis of the same problem.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these works, criteria for the prediction of the onset of transition based on integral boundary layer quantities (the Abu-Ghannam and Shaw [9] or the Mayle model [1], which are both used in this work) or the integration of the growth rates of instability waves (the so-called e N model [4]) have been used. A few works in which the onset of transition was deÿned by the user can also be found (for instance Reference [5], using the SA model). As far as transition criteria are concerned, the previous works have shown that none of the aforementioned ones is clearly superior.…”
Section: Introductionmentioning
confidence: 99%